FUNGSI ANGGARAN PENDAPATAN DAN BELANJA DESA DALAM PEMBANGUNAN DESA DI DESA BORONA KECAMATAN IBU UTARA KABUPATEN HALMAHERA BARAT - Bassy, Hendrisfayor (HOLISTIK, Journal Of Social and Culture, 2013)
Incomes and expenditure function of rural development in Desa Borona Kecamatan Ibu Utara Kabupaten Halmahera Barat, cannot walk properly because of the low public participation in planning, implementation and monitoring. It is seen also from the low level of education, mastery of tasks and work discipline, affecting the smooth implementation of development in the village. For all of the elements contained in Desa Boroma heads and village device, BPD, LPM, Karang Taruna, Tim PKK and the community should participate in APBDes function, so that the construction carried out in the village. Keywords: APBDes function, community participation, rural development